Changes in rat liver microsomal enzyme activities induced by injection of rat liver growth factor into male rats - García Cañero, Rafael; Pérez de Diego, Javier; Trilla, Carolina; de Foronda, Miguel; Díaz-Gil, Juan José; Cereceda, Rosa M.; Guijarro, Maricarmen (My University, 2024)
Microsomal cytochromes P450 and b5 and enzyme activities linked to P450 isoforms , , IIC11 and IIIA were assessed over a 72 h period in male Wistar rats after intraperitoneal injection of a single dose of 4 ¿g/100 g body weight of rat liver growth factor (r-LGF) and compared with those of partially hepatectomized and sham-operated animals. The injection provoked a marked decrease in the activities of cytochrome P450 isozymes , IIC11 and IIIA and about a 50% reduction in cytochrome P450 and b5 contents during the first 48 h postinjection, which were slowly restored to the levels observed in control or sham-operated animals. The findings in partially hepatectomized rats were similar. These results suggest that, alone, the rat liver growth factor selectively mimics the effects of the initial stages of in vivo liver regeneration in certain hepatic microsomal detoxifying enzymes.